Analysis of the Influence of Fraud Diamond Dimensions on Fraudulent Behavior of Accounting Students at Diponegoro University - Andrean Seto Nurdiansyah; NPMA Durya; Fusi Rachele (Yayasan Adra Karima Hubbi, 2023)
This study aims to determine the effect of the fraud diamond dimension on the fraudulent behavior of accounting students at Diponegoro University. Cheating is a fraudulent act committed by someone to gain profit for himself by taking advantage of other people. The data analysis technique in this study was multiple linear regression analysis using data from Diponegoro University accounting student respondents in the 2019 and 2020 batches. The results showed that pressure and ability had an effect on academic cheating, while opportunity and rationalization had no effect on academic cheating. The results of the model feasibility test show that pressure, opportunity, rationalization and ability simultaneously influence the academic fraud of accounting students at Diponegoro University.